2015
DOI: 10.1080/23723556.2015.1087452
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of mitofusin-2 by sirtuin-1: A critical event in cell survival after ischemia

Abstract: Sirtuin-1 (SIRT1) is associated with longevity and cell survival. Recently, we unveiled a new role of SIRT1 in hepatic ischemia/reperfusion (I/R) injury and identified a novel interaction between SIRT1 and mitochondrial outer membrane protein mitofusin-2 (MFN2), in which SIRT1-dependent deacetylation of MFN2 regulates mitochondria and autophagy in the liver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…4A and C ). Furthermore, several studies have suggested that Sirtuin 1 (SIRT1) is the upstream inducer of Mfn2 expression ( 45 ), and therefore, we aimed to ascertain whether SIRT1 is involved in Mfn2 regulation by Yap. Firstly, we found that loss of Yap was associated with the downregulation of SIRT1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4A and C ). Furthermore, several studies have suggested that Sirtuin 1 (SIRT1) is the upstream inducer of Mfn2 expression ( 45 ), and therefore, we aimed to ascertain whether SIRT1 is involved in Mfn2 regulation by Yap. Firstly, we found that loss of Yap was associated with the downregulation of SIRT1 ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These findings suggest that nucleo-cytoplasmic shuttling of Sirt1 and Sirt1–Rb co-localization play an important role in HX-induced OPC proliferation. Since the predominantly nuclear Sirt1 also regulates basal proliferation, it is possible that HX-induced Sirt1 translocation need not be restricted to proliferation, and suggests inclusion of metabolic targets, including mitofusin-2, whose deacetylation regulates mitochondrial function and cell death after ischaemic/reperfusion injury59.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that SIRT1 was depleted by free fatty acids and, in turn, SIRT1-dependent deacetylation of mitofusin 2, a protein critical for maintaining mitochondrial integrity and functioning. [ 53 ].…”
Section: Role Of Mitochondrial Dysfunction In Liver Diseasesmentioning
confidence: 99%